Korelasi Antara Tecnological Pedagogical And Content Knowladge (TPACK) Dengan Kinerja Mengajar Dosen - Putri, Dian Puspita Eka (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2021)
Abstract This research aims to examine the relationship between the technological, pedagogical, content and knowledge capabilities of lecturers in the IAINsyaikh Abdurrahman Siddik Bangka Belitung environment and lecturer performance. As for the results of this study, there is a positive and significant relationship between Technological Knowledge and the teaching performance of lecturers at IAIN Syaikh Abdurrahman Siddik Bangka Belitung. This is indicated by the calculated correlation coefficient being greater than r table or 0.438 > 0.36 and a significance value of 0.015 <0.05. There is a positive and significant relationship between Pedagogical Knowledge and the teaching performance of lecturers at IAIN Syaikh Abdurrahman Siddik Bangka Belitung. This is indicated by the calculated correlation coefficient which is greater than r table, namely 0.827> 0.36 and a significance value of 0.00 <0.05. There is a positive and significant relationship between content knowledge and the teaching performance of IAIN Syaikh Abdurrahman Siddik lecturers. This is indicated by the calculated correlation coefficient being greater than the r table, namely 0.827 > 0.36 and a significance value of 0.00 <0.05.Keywords: deaf media, prayer procedures and readings keywords: TPACK, Performance, Lecturer Abstrak Penelitian ini bertujuan untuk menguji hubungan antara kemampuan technological, pedagogical, content dan knowladge dosen - dosen dilingkungan IAINsyaikh abdurrahman siddik bangka belitung dengan kinerja dosen. adalapun hasil dari penelitian ini adalah Terdapat hubungan positif dan signifikan antara Technological Knowledge dengan kinerja mengajar dosen IAIN Syaikh Abdurrahman Siddik Bangka Belitung. Hal ini ditunjukkan dengan koefisien korelasi hitung lebih besar dari r tabel atau 0,438 > 0,36 dan nilai signifikansi 0,015<0,05. Terdapat hubungan positif dan signifikan antara Pedagogical Knowledge dengan kinerja mengajar dosen IAIN Syaikh Abdurrahman Siddik Bangka Belitung. Hal ini ditunjukkan dengan koefisien korelasi hitung lebih besar dari r tabel yaitu 0,827>0,36 dan nilai signifikansi 0,00<0,05.Terdapat hubungan positif dan signifikan antara content knowledge dengan kinerja mengajar dosen IAIN Syaikh Abdurrahman Siddik. Hal ini ditunjukkan dengan koefisien korelasi hitung lebih besar dari r tabel yaitu 0,827 > 0,36 dan nilai signifikansi 0,00<0,05. kata kunci: TPACK, Kinerja , Dosen